THE USE OF CONTEXTUAL TEACHING AND LEARNING METHOD IN TEACHING ENGLISH AT THE EIGHTH GRADE OF MTS NEGERI TELUKDALAM - Nazara, Masni Ridha (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
Contextual Teaching and Learning is a learning concept that used by teachers to relate the subject with students real world situation. The main purpose of this study were (1) to describe the use of contextual teaching and learning (CTL) method in teaching English, and (2) to find out the problems that faced by the teacher in implementing Contextual Teaching and Learning (CTL) in teaching English at the eighth grade of MTs Negeri Telukdalam. The research used the qualitative method. From the data analyzed, (1) the implementation of CTL has implemented through some components of CTL: contructivistic, inquiry, questioning, learning community, modelling, reflection and authentic assessment. (2) the problems faced by the teacher were the limitation of textbooks, time allocation and students lack of understanding on materials. Contextual teaching and learning (CTL) method is quite helpful for teacher in explaining the material and also encourage students who are creative to think critically. In contextual teaching and learning (CTL) method it is suggested for teacher that in teaching learning activities, not only provide material theoretically but also relate it with students real-world situations, so that students understandthe material and can apply it in everyday life.